2019
DOI: 10.29137/umagd.486921
|View full text |Cite
|
Sign up to set email alerts
|

Lavanta (Lavandula angustifolia) Katkısının Yonca Silajlarının Kalitesi Üzerine Etkisi

Abstract: Öz Bu çalışmada, farklı düzeylerde ilave edilen lavanta (Lavandula angustifolia) çiçek +sapının yonca silajlarının kalitesi üzerine etkileri araştırılmıştır. Araştırmada, silaj katkı materyalini oluşturan lavantanın çiçeği ve sapı eşit düzeylerde (% 50 + % 50) karıştırılarak kullanılmıştır. Lavanta (çiçek + sap) yonca silajlarına % 0 (kontrol), 0.5, 1.0, 1.5 ve 2.0 düzeylerinde ilave edilmiştir. Araştırma sonunda, % 2 lavanta ilavesiyle yonca silajlarının NDF içerikleri artmıştır (P<0.05). KM, OM, ADF ve HP iç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…The ash content of the silages was observed to be higher in OP5 (15.80%) than the control (14.02%) and similar to OP3 (14.76%) on a DM% basis (Table 2; p<0.05). Soycan-Önenç and Turgud (2019) found that the DM contents of the silages did not change with the additive as a result of the addition of oregano essential oil to alfalfa silage, and the addition of lavender essential oil to alfalfa silage (Duru, 2019). In the study, although the silage material was ensiled and well preserved in the DM range recommended for silage feeds, DM loss occurred in the groups to which additives were added.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The ash content of the silages was observed to be higher in OP5 (15.80%) than the control (14.02%) and similar to OP3 (14.76%) on a DM% basis (Table 2; p<0.05). Soycan-Önenç and Turgud (2019) found that the DM contents of the silages did not change with the additive as a result of the addition of oregano essential oil to alfalfa silage, and the addition of lavender essential oil to alfalfa silage (Duru, 2019). In the study, although the silage material was ensiled and well preserved in the DM range recommended for silage feeds, DM loss occurred in the groups to which additives were added.…”
Section: Resultsmentioning
confidence: 76%
“…It was reported that the physical quality properties of silages prepared with the contribution to meadow grass of forage locust flakes increased (Atalay, 2015). It is stated that the silage quality criteria of lavender oil contribution to alfalfa forage were determined as satisfactory (Duru, 2019). Özturk et al (2020) is reported that mixtures in hops with corn and forage soybean were obtained as "good" and "very good" silage quality classes.…”
Section: Resultsmentioning
confidence: 99%
“…This disturbance may become chronic and persist for months or even years after cancer treatment is completed. In addition, sleep disturbances are also caused by physical illness or pain, psychological disorders, medication, depression, fatigue, and anxiety, hence, it is widely concerned as the second most difficult disorder to treat (Fiorentino, 2011;Arslan & Fadıloğlu, 2009;Stone & Minton, 2008). The sleep system is integrated with several aspects of human physiology, such as cell metabolism, cardiovascular function, cognitive function, and immune function (Dierickx et al, 2018).…”
Section: Introductionmentioning
confidence: 99%